ISLAMIC PRINCIPLES IN REAL ESTATE DEVELOPMENT: A MASS APPRAISAL PERSPECTIVE - Mat Noor, Noorsidi Aizuddin; Deris, Farhana Diana; Wan Ismail, Wan Ibrisam Fikry; Abdul Hamid, Hamdi; Mokhtar, Afizan (Journal of Islamic, Social, Economics and Development, 2024)
This study aims at analysing the application of Shari’ah compliance in real estate development and mass appraisal in Malaysia. The importance of this topic is also based on the need to discuss the ethical questions and social inequalities that are caused by mainstream real estate practices that are oriented on profit increase only. The first research question is derived from the fact that there exists a dearth of empirical research on how principles of justice, equity, and social responsibility that are hallmarked by Islamic business can be adopted in real estate to uphold ethical standards in society. Some of the principles of Islamic finance, like the prohibition of riba and speculative investments to enhance property valuation and development has been identified. The present study used both quantitative surveys of 150 real estate practitioners and mass appraisal specialists and qualitative interviews with 15 Islamic finance experts. The study shows that 70% of the real estate practitioners and 60% of the mass appraisal specialists are aware of the benefits of applying Islamic principles in their professions. But there are still some issues, such as the fact that it requires rather radical changes in existing business processes and requires proper education in the sphere of Islamic finance. These findings indicate that the real estate industry can be positively changed by the adoption of Islamic principles in ethical practice, relation to the community, and proper property valuation. This study enriches the real estate literature by offering a conceptual model that incorporates Islamic principles in order to enhance the sustainable development of cities and solve the problem of housing affordability in Malaysia. Hence, the implementation of these principles may contribute towards improving the real estate sector and its sustainability, as well as society.